2020
DOI: 10.1007/s42995-020-00036-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and tomographic description of marlin sucker Remora osteochir, Pisces: Echeneidae—preliminary data of one specimen

Abstract: Remoras are commensal fish of various marine species, such as sharks, swordfishes, turtles, dolphins, manta rays and whales. One specimen of marlin sucker Remora osteochir was evaluated using computed tomography for skeletal digital reconstruction, digital radiology for general evaluation and bone counting, and the double contrast technique to distinguish coelomic organs. In radiographic images, it was possible to observe otoliths in the center of the neurocranium, to count 27 vertebrae, nine pairs of ribs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They are mainly composed of micron-sized stiff hairs that protrude from individual comb-tooth lamellae and terminate as sharp cone-shaped points of varying shapes [ 69 ]. Studies have shown that a style can significantly increase the resistance between the sucker of the remora and the hosts’ uneven local surfaces to sliding, thereby enhancing its friction and shearing strength [ 70 , 71 ]. As the comb lamellae rotate in a direction, the style can withstand exposure to the large shearing force caused by the movement and avoid being thrown off by the hosts.…”
Section: Non-smooth Structural Morphologies and Attachment Mechanisms...mentioning
confidence: 99%
“…They are mainly composed of micron-sized stiff hairs that protrude from individual comb-tooth lamellae and terminate as sharp cone-shaped points of varying shapes [ 69 ]. Studies have shown that a style can significantly increase the resistance between the sucker of the remora and the hosts’ uneven local surfaces to sliding, thereby enhancing its friction and shearing strength [ 70 , 71 ]. As the comb lamellae rotate in a direction, the style can withstand exposure to the large shearing force caused by the movement and avoid being thrown off by the hosts.…”
Section: Non-smooth Structural Morphologies and Attachment Mechanisms...mentioning
confidence: 99%